Crimes Against Agriculture: NAFTA as State Crime in Mexico. (8th November 2022) - Patten, Daniel
Abstract : With the implementation of NAFTA in 1994, several consequences have followed. The current study is a case study of the negative harms primarily felt by Mexican farmers. Using the copious research on NAFTA, the trade deal is shown to have ingratiated transnational corporations while leaving poor rural farmers to cope for themselves in a newly shaped economy. Using anomie-strain theory, social structure of accumulation theory, and the concept of a criminogenic policy, NAFTA is contextually situated and connected to its harmful effects, contributing to poverty, under- and unemployment, displacement of rural farmers, the destruction of small-scale corn growers, malnutrition via the neoliberal diet, and a loss of Mexican food sovereignty. Nearly three decades after NAFTA, ignorance of such effects should not be possible in light of negotiating new or renegotiated old trade deals. Researchers of state crime must build an understanding of how policy is a tool of state crime.